Water use in four model tropical plant associations established in the lowlands of Costa Rica - Marco V Gutiérrez-Soto; John J Ewel (Revista de Biología Tropical, 2008)
We examined soil water use patterns of four model plant associations established in the North Caribbean lowlands of Costa Rica by comparing the stable hydrogen isotope composition, δD, in xylem sap and in soil water at different depths, under rainy and dry conditions. Four 5-year-old model plant associations composed of 2 tree species (Hyeronima alchorneoides and Cedrela odorata) having different architecture and phenology were studied. Average tree height was 8.9 and 7.6 m, respectively. Each tree species was grown in monoculture and in polyculture with 2 perennial monocotyledons (Euterpe oleracea and Heliconia imbricata). Maximum rooting depth at the time of δD determination was ~ 2 m for almost all species. Most roots of all species were concentrated in the upper soil layers. Stomatal conductance to water vapor (gS) was higher in the deciduous C. odorata than in the evergreen H. alchorneoides; within each species, gS did not differ when the trees were grown in mono or in polyculture. During the rainy season, gradients in soil water δD were not observed. Average rainy season xylem sap δD did not differ among members of the plant combinations tested (-30 ‰), and was more similar to δD values of shallow soil water. Under dry conditions, volumetric soil water content declined from 50 to ~ 35%, and modest gradients in soil water δD were observed. xylem sap δD obtained during dry conditions was significantly lower than rainy season values. xylem sap δD of plants growing in the four associations varied between -9 and -22‰, indicating that shallow water was predominantly absorbed during the dry period too. Differences in xylem sap δD of trees and monocots were also detected, but no significant patterns emerged. The results suggest that: a) the plant associations examined extracted water predominantly from shallow soil layers (<1 m), b) the natural isotopic variation in soil and plant water at the study site was low, and c) the plant mixes obtain water from more than a single soil layer simultaneously. Temporal factors were important in determining the competition and complementary relations observed among the trees and the perennial monocots. Under the prevailing environmental conditions, water use in these plant associations was determined largely by species-specific attributes such as biomass allocation to fine roots, phenology, and canopy architecture, and to a lesser extent by water limitations. Rev. Biol. Trop. 56 (4): 1947-1957. Epub 2008 December 12. Examinamos los patrones de uso de agua del suelo de cuatro asociaciones vegetales establecidas en el Caribe norte de Costa Rica, comparando la composición isotópica del hidrógeno, δD, en la savia del xilema y en el agua del suelo en condiciones lluviosas y secas. Estudiamos cuatro asociaciones de cinco años de edad compuestas por dos árboles (Hyeronima alchorneoides y Cedrela odorata) con diferente arquitectura y fenología, cultivados en mono y policultivo con dos monocotiledóneas perennes (Euterpe oleracea y Heliconia imbricata). Las excavaciones mostraron que la profundidad máxima de las raíces fue de 2 m para casi todas las especies, y que la mayor densidad de raíces se encontraba en la superficie del suelo. La conductividad estomática (gS) fue mayor en el árbol caducifolio (C. odorata) que en el perennifolio (H. alchorneoides); dentro de cada especie, gS no difirió cuando los árboles fueron cultivados en mono o en policultivo. Los resultados sugieren que: a) las asociaciones examinadas extrajeron agua predominantemente de las capas superficiales del suelo (<1 m), b) la variación natural en el acceso al agua del suelo por parte de las especies, y en las propiedades del suelo, fue baja, y c) las combinaciones de plantas obtuvieron agua de varias capas del perfil del suelo simultáneamente. Los factores relacionados con el tiempo fueron importantes en la determinación de las relaciones de competencia y complementariedad observadas entre los árboles y las monocotiledóneas perennes. En las condiciones ambientales prevalecientes, el uso del agua por parte de estas asociaciones de plantas fue determinado más por atributos, como la asignación de biomasa a las raíces finas, la fenología, y las propiedades del dosel, que por limitaciones en la disponibilidad de agua.